Palácio Rio Branco: o palácio que virou museu - Viana, Ana Paula Bousquet (2011)
This dissertation aims to regain some of the trajectory of the Rio Branco Palace turned into museum, due its strong cultural and symbolic role within the state of Acre. The research focuses on the creation of a museum in 2002 in the premises of the Rio Branco Palace. Through its permanent exhibit collection it invites the reader to an immersion in some historical moments of the formation of the society of Acre. The research is intended above all to disclose the state of Acre and its culture. The Palace as a symbol of the larger society of Acre and the museum.